Cytotoxicity Evaluation of Ammonia-Modified Graphene Oxide Particles in Lung Cancer Cells and Embryonic Stem Cells. (3rd October 2018) - Keremidarska-Markova, Milena; Hristova-Panusheva, Kamelia; Andreeva, Tonya; Speranza, Giorgio; Wang, Dayong; Krasteva, Natalia
Abstract : Potential toxicity of graphene oxide (GO) is a subject of increasing research interest in the recent years. Here, we have evaluated the cytotoxicity of ammonia-modified GO (GO-NH2 ) and pristine GO particles in human lung cancer cells, A549 and embryonic stem cells, Lep3 exposed to different particles concentrations (0.1, 1, 10, 20, and 50 μ g/ml) for different times (24 and 48h). Compared with GO, GO-NH2 particles possessed smaller size, positive surface charge and higher thickness. An increased propensity to aggregation in cell cultures was also found for GO-NH2 particles. Cytotoxicity evaluation revealed that GO-NH2 particles are more toxic than pristine GO. Applied at concentrations of 10, 20 and 50 μ g/ml for 24h they affect significantly cell morphology of viable embryonic stem cells whereas human lung cancer A549 cells seem to be relatively more resistant to short-time exposure. After 48h exposure however cell proliferation of A549 cells was strongly suppressed in a dose-dependent manner while the proliferation ability of embryonic stem cells was not affected. These results suggested that both GO particles exert different degree of cytotoxicity which is time, dose and cell dependent. In general, ammonia-modified GO particles are more toxic than the pristine GO which should be taken into account for future biomedical applications.